The secret country / 1. - Johnson, Jane, 1951- (Johnson, Jane, 1951- Eidolon chronicles, 2006)
Having learned from a talking cat that he and his sisters are the half-elfin royalty of a parallel world called Eidolon, twelve-year old Ben Arnold attempts to stop his evil uncle from smuggling magical creatures between the two worlds to sell on the black market.